The styrene purification performance of biotrickling filter with toluene-styrene acclimatization under acidic conditions. (3rd August 2019) - Li, Kang; Zhou, Jiazhen; Wang, Liping; Mao, Zhen; Xu, Ruiwei
ABSTRACT: The obvious disadvantages of biotrickling filters (BTFs) are the long start-up time and low removal efficiency (RE) when treating refractory hydrophobic volatile organic compounds (VOCs), which limits its industrial application. It is worthwhile to investigate how to reduce the start-up period of the BTF for treating hydrophobic VOCs. Here, we present the first study to evaluate the strategy of toluene induction combined with toluene-styrene synchronous acclimatization during start-up in a laboratory-scale BTF inoculated with activated sludge for styrene removal, as well as the effects of styrene inlet concentration (0.279 to 2.659 g·m −3 ), empty bed residence time (EBRT) (i.e., 136, 90, 68, 45, 34 sec), humidity (7.7% to 88.9%), and pH (i.e., 4, 3, 2.5, 2) on the performance of the BTF system. The experiments were carried out under acidic conditions (pH 4.5) to make fungi dominant in the BTF. The start-up period for styrene in the BTF was shortened to about 28 days. A maximum elimination capacity (ECmax ) of 126 g·m −3 ·hr −1 with an RE of 80% was attained when styrene inlet loading rate (ILR) was below 180 g·m −3 ·hr −1 . The highest styrene RE(s) [of BTF] that could be achieved were 95% and 93.4%, respectively, for humidity of 7.7% and at pH 2. A single dominant fungal strain was isolated and identified as Candida palmioleophila strain MA-M11 based on the 26S ribosomal RNA gene. Overall, the styrene induction with the toluene-styrene synchronous acclimatization could markedly reduce the start-up period and enhance the RE of styrene. The BTF dominated by fungi exhibited good performance under low pH and humidity and great potential in treating styrene with higher inlet concentrations. Implications : The application of the toluene induction combined with toluene-styrene synchronous acclimatization demonstrated to be a promising approach for the highly efficient removal of styrene. The toluene induction can accelerate biofilm formation, and the adaptability of microorganisms to styrene can be improved rapidly by the toluene-styrene synchronous acclimatization. The integrated application of two technologies can shorten the start-up period of biotrickling filters markedly and promote its industrial application.